Case 3294. Gynacantha Rambur, 1842 and Triacanthagyna Selys, 1883 (Insecta, Odonata): proposed conservation of usage by designation of Gynacantha nervosa Rambur, 1842 as the type species of Gynacantha - Von Ellenrieder, Natalia (2005)
The purpose of this application, under article 70.2 of the Code, is to conserve the accustomed usage of the names Gynacantha Rambur, 1842 and Triacanthagyna Selys, 1883 for two genera of aeshnid dragonflies. The names are objective synonyms but are currently in use for two distinct groups of species. It is proposed that Gynacantha Rambur 1842 should be designated as the type species of Gynacantha.